AN ANALYSIS OF DANIEL MARTIN BY JOHN FOWLES: A POSTMODERN NOVEL WITH THE ASPECTS OF THE VICTORIAN BILDUNGSROMAN - Koseoglu, Berna (PEOPLE: International Journal of Social Sciences, 2017)
John Fowles, one of the most significant post-war English novelists, produced remarkable postmodern novels in which he combined fiction with history. Dealing with the concepts of internal exile, individual isolation and loneliness, he dwelt on duality, fragmentation, discontinuity, the combination of the past and the present and the search of the individual for whole sight. His novel, Daniel Martin, portrays these features, however it not only includes these aspects of postmodern novels, but it also acquires the significant characteristics of the Victorian Bildungsroman, one of the remarkable types of realistic novels. Thus, the aim of this study is to identify the combination of realism and postmodernism in Daniel Martin in the light of the struggles of the protagonist, who tries to eliminate his fragmented identity and to achieve a sense of wholeness, so in this paper the characteristics of postmodern novels will be analyzed together with the traits of the Bildungsroman by concentrating on the relationship between history and fiction.